Three-dimensional photocatalysts with a network structure. Issue 12 (1st March 2017) - Jiang, Wenjun; Zhu, Yongfa; Zhu, Guoxiang; Zhang, Zijiang; Chen, Xianjie; Yao, Wenqing
Abstract : The synthetic strategies and energy and environmental applications of 3D network photocatalysts are summarized and the ongoing challenges and perspectives are highlighted. Abstract : Three-dimensional (3D) photocatalysts with a network structure are presently attracting enormous research interests due to their excellent properties, such as a high specific surface area, high adsorptive capacity, high structure stability, low gas resistance and a large number of exposed active sites, which suggest it could act as a promising candidate for solar energy conversion or environmental pollution elimination. This review first introduces the limiting factors for the photocatalytic efficiency of such photocatalysts and the corresponding solutions. Then, the superiorities of 3D network photocatalysts are highlighted. Importantly, we summarize the most common 3D photocatalysts and their synthetic strategies. Furthermore, the most important applications, including solar energy storage and conversion and photocatalytic pollutant degradation, are also discussed. Finally, this review presents some perspectives concerning the challenges and new directions of 3D photocatalysts with a network structure.